2018
DOI: 10.1097/nmd.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Types of Trauma, Posttraumatic Stress Disorder, and Academic Performance in a Population of University Students

Abstract: The aim of this work was to investigate the association between traumatic experiences and posttraumatic stress disorder (PTSD) with the academic performance of university students. This is a one-phase study that included 2213 students, enrolled at one of seven college institutions in their first or final semesters in all programs, who filled out the self-response questionnaires. From this student population, 14% presented with PTSD, with 13.3% in their first semester and 14.9% in their final semester. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…26 One possible mechanism is that a proportion of individuals who have been exposed to trauma suffer from PTSD, which can severely impair a person's executive function. 28 Regarding the relationship between PTSD and AP, some studies showed that students with higher self-reported PTSD symptoms were prone to having lower GPAs, 29 students with lower AP had a higher prevalence of PTSD, 30 and PTSD was associated with lower odds of achieving each of the educational milestones during the study period. 31 Nevertheless, results from other studies found that the direct correlation between PTSD and AP was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…26 One possible mechanism is that a proportion of individuals who have been exposed to trauma suffer from PTSD, which can severely impair a person's executive function. 28 Regarding the relationship between PTSD and AP, some studies showed that students with higher self-reported PTSD symptoms were prone to having lower GPAs, 29 students with lower AP had a higher prevalence of PTSD, 30 and PTSD was associated with lower odds of achieving each of the educational milestones during the study period. 31 Nevertheless, results from other studies found that the direct correlation between PTSD and AP was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…14 The deleterious implications of PTSD for educational performance have been suggested in a small number of primarily crosssectional studies. [15][16][17][18][19] Longitudinal studies have been even scarcer but also suggest that PTSD can impair educational performance. 17,19 Although informative, these previous studies [15][16][17][18][19] had several limitations, including crosssectional designs, focus on a single educational milestone, generally small samples, self-reported educational achievements, or insufficient control of important confounders (eg, familial factors, psychiatric comorbidity, and general cognitive ability).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the United States placed PTSD prevalence among their college students at 19–20% (Berenz et al, 2016 ; Fortney et al, 2016 ). Finally, low prevalence rates of PTSD were reported in studies that targeted university students in Kenya (15.8%) Othieno et al, 2015 ) and Brazil (14.0%) (Pereira et al, 2018 ).…”
Section: Discussionmentioning
confidence: 97%
“…PTSD symptom clusters were divided into the following: 1 – re-experiencing memory, 1 – persistent avoidance, 2 – negative alternations in mood and cognitions, and 2 – alterations in arousal and reactivity, with a score between 31 and 33 was considered significant for meeting probable diagnosis criteria of PTSD based on instrument standards (Othieno, Okoth, Peltzer, Pengpid, & Malla, 2015 ). For this study, we used the Arabic version of PCL-5 that was validated for evaluating PTSD in a previous study (Pereira et al, 2018 ). The English and Arabic versions of the questionnaire and PCL-5 are available in Appendix 1.…”
Section: Methodsmentioning
confidence: 99%